Justiça penal negociada e criminalidade macroeconômica organizada: o papel da política criminal na construção da ciência global do Direito Penal - Turessi, Flávio Eduardo (2019)
The present work aims to recover and value the role of criminal policy as an instrument to deal with organized macroeconomic crime, a subsystem especially highlighted in this study. To this end, it is based on the premise that the crisis experienced by contemporary criminal law is not restricted to its dogmatic limits. In fact, he takes care of a crisis of scientific validity that imposes reflections on his method and reaches, much more broadly, his social identity. The very evolution of the modern models of the State of Law lived through the centuries, from the Liberal State to the democratic State, passing through the social State of Right, reveals, along with the variability that marks the conformation of fundamental human rights, the need of the evolution of the Criminal Law itself as an instrument of protection of goods and values dear to a particular social body. The Criminal Law, which is governed by a democratic State of Law, which sees in the dignity of the human person its fundamental hypothetical value, and which presents as fundamental rights, alongside negative public liberties, supraindividual rights, should not be the same Criminal Law operated by a an outmoded model of the late eighteenth century, markedly neutral and absentee, who saw in the State itself the illustrative figure of Leviathan by Thomas Hobbes. The traditional solipsistic view of criminal law is insufficient to understand and satisfactorily control the phenomenon of modern organized macroeconomic crime, fed by socioeconomic transformations such as globalization and multiculturalism, with the present study suggesting the need to application of Criminal Law as "Global Science", and not only as isolated dogmatic, under penalty of aggravation of its crisis that insists on giving it the pecha of mere anachronistic and symbolic instrument of social control. Thus, with the background of the "Global Science of Criminal Law" thesis, with its undisputed multidisciplinary content, its postulates are tested in the face of the need to give rationality to the production of criminal laws designed to deal with so-called criminality macroeconomic policy and anticompetitive behavior contained therein, with particular emphasis on the formation of a cartel, because of its manifestly social and multi-standard legislative treatment conferred by national and international legal order. Finally, the present study demonstrates that confronting organized macroeconomic crime, in order to be minimally efficient, swift and effective, should broaden the spaces of consensus between the accuser and the criminal, stimulating the application of a negotiated Criminal Justice as a form of policy criminal, but without losing sight of the postulate of proportionality, in its facet of prohibition of insufficient criminal protectio